The functional food product on the basis of topinambur - L. K. Patsyuk; T. V. Fedosenko; E. A. Medvedeva; T. V. Narinian (Аграрная наука Евро-Северо-Востока, 2018)
This research was aimed at the development of a recipe for a multi-functional topinambur-based product in order to create a new range of products having good sensory characteristics. The recipes for a new type of functional canned food product “Dessert from topinambur”, consisting of a mixture of vegetables and fruits with good organoleptic characteristics were developed. Also the experimental samples were produced and their physical and chemical as well as organoleptic characteristics have been determined. The development of recipes was based on the requirements of GOST R 52349-2005 “Functional food products”, which says that each portion of the functional product must contain at least 15% of the daily consumption rate established by the Institute of nutrition of the RAMS for a specific physiological functional ingredient. To select the best recipe of the dessert the comparative experimental samples of canned food with the content of topinumbur from 30 to 45% as the main component were made. As the best composition of canned food “Dessert from topinambur”, which received an average rating of 4.5 points as a result of sensory analysis by rating, the following content of components was chosen: topinambur puree - 40%, pureed carrots - 30%, pureed apples - 30%. According to the results of sensory evaluation of the intensity of the characteristics the profiles for each of the five indicators were built: the taste, the color, the aroma, the appearance and the consistency. Also the diagram of the overall organoleptic evaluation of a new type of functional product “Dessert from topinambur” was built.